Design and synthesis of new anticancer pyrimidines with multiple-kinase inhibitory effect - El-Deeb, Ibrahim Mustafa; Lee, So Ha (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
A new series of N-substituted-2-aminopyrimidines based on the '4-(pyridin-3-yl)pyrimidin-2-amine' scaffold of Imatinib has been designed and synthesized. A selected group from the target compounds was tested over a panel of 60 cancer cell lines at a single dose concentration of 10 mu M, and the two most active compounds, 25b and 30, were further tested in a five-dose testing mode to determine their IC50 values over the 60 cell lines. Compound 30 has showed good potencies and high efficacies, and was accordingly tested at a single dose concentration of 10 mu M over a panel of 54 kinases. At this concentration, the compound has showed multiple inhibitions over a number of oncogenic kinases, including ABL1, AKT1, LCK, C-SRC, PIM1, FLT3, FYN, and KDR. A molecular modeling study was made by docking of the most active compound 30 and its inactive analog 29 into the kinase domain of ABL1 to investigate their possible binding interactions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: TYROSINE KINASE; EXPRESSION; GROWTH; DERIVATIVES; ACTIVATION; POTENT